Credit Risk Determinants in Regional Development Banks: Intermediation, Capital Structure, and Gender Governance - L. Lutfi; Kadek Irma Susanti (Golden Ratio of Finance Management, 2026)
This research analyzes how credit growth, capitalization, and profitability influence credit risk in Indonesian Regional Development Banks (Bank Pembangunan Daerah, hereafter BPDs), additionally investigating the moderating influence of female commissioners. Based on Agency Theory and Resource Dependence Theory, it suggests that both financial performance and board governance structures affect banks’ willingness to take risks and their credit risk results. Using a quantitative approach, the study analyzes panel data from 23 conventional BPDs in Indonesia over the 2018–2024 period through panel data regression, generating 161 bank-year observations. The hypotheses are tested using panel data regression with the Random Effects Model (REM), selected through panel model specification tests. The findings indicate that the expansion of loans and the enhancement of profits notably diminish credit risk, suggesting that cautious lending practices and improved financial performance contribute to better credit quality and risk management. Capital adequacy exhibits a positive yet inconsequential link to credit risk, implying that holding more capital may lead to increased risk-taking behavior. The presence of female commissioners does not significantly influence credit risk and does not affect the relationship between loan growth, capital adequacy, or profitability. In summary, the model demonstrates statistical significance and accounts for 17.06% of the variation in credit risk. Female commissioners have minimal impact on credit risk and its relation to financial factors, indicating limited influence of board gender diversity on oversight. The study enriches banking risk literature by showing that female board representation has limited governance impact in emerging-market regional banks without substantial decision-making power.